Utility of Redox Reaction for Spectrophotometric Determination of Propranolol and Isoxuprine Hydrochlorides in Pure and Dosage Forms - S. Al-Attas, Amiraqh (Asian Journal of Chemistry, 2010)
Two simple, accurate and sensitive spectrophotometric procedures for the assay of propranolol hydrochloride (PPH) and isoxsuprine hydrochloride (ISH) in pure and in dosage forms have been proposed the methods are based on the oxidation of the drug by a known excess of standard N-bromosuccinimide (NBS) (method A) or by cerium (IV) sulfate (method B), in an acidic medium followed by the reaction of excess oxidant with amaranth dye (A17) or rhodamin 6G (Rh6G), respectively. The Absorbance values described linearly with increasing drug concentration regression analysis of Beer’s plots showed good correlation in the concentration range of 0.2-6.4 μg mL-1. The apparent molar absorptivity, Sandell sensitivity, detection and quantification limits were calculated. From more accurate analysis, Ringbom optimum concentration ranges were employed successfully in the range 0.4-6.0 μg mL-1. Analyzing pure and dosage forms containing (PPH) and (ISH) tested the validity of the proposed procedures. The relative standard deviations were ≤ 1.70 with recoveries 98.75-101.0%.